2020
DOI: 10.1127/fal/2019/1242
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of freshwater sponges in Serbia

Abstract: As data on the distribution of freshwater sponges (Porifera, Demospongiae, Spongillida) in Serbia are extremely scarce, we investigated the main Serbian rivers and lakes with respect to Porifera occurrence, for which 17 lotic and 11 lentic water bodies were selected. Sponges were found in 11 of 17 rivers (62 specimens in total) and in 3 of 11 lakes/reservoirs (seven specimens in total). Classical morphological spicule analysis was coupled with polymerase chain reaction (PCR) and gene sequencing for species id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous investigations of Serbian waters revealed mainly Spongilla lacustris (Linnaeus, 1759) species, sporadically found in the benthic macroinvertebrate communities of large rivers (Globaqua, JDS3 report). Recent studies on freshwater sponges of the western Balkans and some parts of the Pannonian Plain by Andjus et al [11,12] confirmed the presence of five species in different water bodies.…”
Section: Introductionmentioning
confidence: 93%
“…Previous investigations of Serbian waters revealed mainly Spongilla lacustris (Linnaeus, 1759) species, sporadically found in the benthic macroinvertebrate communities of large rivers (Globaqua, JDS3 report). Recent studies on freshwater sponges of the western Balkans and some parts of the Pannonian Plain by Andjus et al [11,12] confirmed the presence of five species in different water bodies.…”
Section: Introductionmentioning
confidence: 93%